(k,n,f) - Arcs in Galois Plane of Order Five - Ban A. Q (College of Education for Pure Sciences, 2006)
In this paper we construct (k,n,f) - arcs of type (n-5,n) in PG(2,5), and we prove that o(ll,7,f) - arc of type (2,7) exist where the points of weight zero form (20,5)- arc and a (6,6,f) - arc of type (1,6) exist where the points of weight zero form (25,5)-arc,